Slanted bilateral lateral rectus recession for convergence insufficiency-type intermittent exotropia: a retrospective study - Meiyu Ren; Qi Wang; Lihua Wang (BMC Ophthalmology, 2020)
Abstract Background The present study sought to investigate the efficiency and safety of slanted bilateral lateral rectus recession for the treatment of convergence insufficiency-type intermittent exotropia. Methods This retrospective study included 34 patients who underwent slanted bilateral lateral rectus recession for convergence insufficiency-type intermittent exotropia in Shandong Provincial Hospital affiliated to Shandong First Medical University between September 2013 and October 2015 with a minimum follow-up of 6 months. A successful surgical alignment was defined as + 5 (positive for esotropia) to − 10 (negative for exotropia) prism diopters (PD) of orthotropia in the primary position while viewing distant or near targets and a near-distance deviation difference ≤ 8PD. Results The mean age of the patients at surgery was 7.09 ± 3.80 years (range, 3 to 18 years). The mean distance deviations were − 26.09 ± 6.5 PD (range, − 15 to − 35 PD) and the mean near deviations, − 37.21 ± 6.3 PD (range, − 25 to − 45 PD) preoperatively. The mean recession amount of upper pole of the lateral rectus was 5.97 mm (range, 4.0 to 7.5 mm) and that of lower pole of the lateral rectus, 7.49 mm (range, 6.0 to 8.5 mm). At a mean follow-up of 15.0 months (range, 6 to 37 months), the surgical success rate was 70.6% (24/34), the under-correction rate was 17.6% (6/34), and the overcorrection rate was 11.8% (4/34). The mean near-distance deviation difference was significantly reduced from 11.12 ± 2.06 PD (range, 10 to 15 PD) preoperatively to 2.47 ± 3.04 PD (range, 0 to 10 PD) postoperatively (P < 0.001). Each millimeter of difference between the upper and lower poles of the lateral rectus recession was associated with an improvement of 5.65 PD in the near-distance deviation difference. At the final follow up, a near-distance deviation difference of ≤8PD was found in 32 (94.1%) patients. None of the patients developed A-V pattern, torsional diplopia, or restricted abduction of the eyes. Conclusions Slanted bilateral lateral rectus recession may successfully reduce the distance and near exodeviations and the near-distance deviation difference, thus was proved to be an effective and safe procedure for the treatment of convergence insufficiency-type intermittent exotropia.